Genre specifics of L. Andreev’s play «The Life of Man» - Сухоруков, Віктор Анатолійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
In article is devoted to the thorough analysis of poetics and genre peculiarities of L. Andreev’s play «The Life of Man». The study showed that the important role in this work play modernistic principles of representation of world and person as neomythologism, intertextuality, motifity, dominating of symbolical types and characters, irony, grotesque. The article “Life of a Man” demonstrated that the “new drama” by L. Andreev has been promoting such a type of conflict, which shows the way of collision, where the Wall resists the Man in its various forms. In the "new myth" of the writer, it turned to Rock (Someone in Gray). Therefore, the basis of the drama "Life of Man" was based on the conflict "Man and Rock", embodied in adequate artistic forms. Thus, the author actively used the semantic potential even more meaningful than in the earlier plays, chronotope, intertextual and auto-intertextual mythosymbolic motifs, as well as the metatextual and artistic possibilities of the frame complex and decoupage, for the formation of the non-mythological level of drama. Describing the drama "Life of Man", the writer called the painting himself, the Parsley (Lubok) theater and the ancient theater with his choir as such forms, which "explained" to the viewer a particular scene. The study of L. Andreev’s drama’s chronotop in various periods of his work, along with variability, demonstrates his apparent conceptual uniformity. The results of our research refute the conception, that approves the evolutional type of Andreev’s dramaturgy from early realistic to “conventional” symbolico-expressionistic drams and drams ‘panpsihe”. Type of the conflict, which lies in its basis, and also all levels of its structure revealed the modernistic nature and isomorphism with Andreev’s prose. Apparently, both in prose, and in dramaturgy of the writer there was no evolution, the accents in the author’s concept only changed and the appropriate art means and image forms merely varied. Already in the first dramas all was put that only came to light, deepened and became more obvious.